Dramatic response and acquired resistance to savolitinib in advanced intrahepatic cholangiocarcinoma with MET amplification: a case report and literature review - Zhou, Kexun; Liu, Yingping; Zhu, Hong (Frontiers in Oncology, 2023)
Background Cholangiocarcinoma (CCA) is an aggressive disease with limited treatment options. Despite substantial efforts to explore better regimens, gemcitabine-based chemotherapy has been the standard first-line treatment for decades. With the growing field of precision medicine, biomarker-guided treatments are gaining popularity. MET alteration is a frequent occurrence in various cancer types, making it a promising target. Case presentation A 53-year-old man visited our hospital with a complaint of upper abdominal pain. Advanced CCA was diagnosed based on the biopsy of the metastatic lymph nodes and immunohistochemistry. Next-generation sequencing revealed MET amplification. As the patient was intolerant to traditional chemotherapy, savolitinib (a c-MET inhibitor) was administered. Partial response was achieved, and the treatment was well tolerated. After 1 year, the patient developed progressive disease, to which the emergence of epidermal growth factor receptor amplification may have contributed. Conclusion Our study verified the therapeutic value of a c-MET inhibitor in advanced CCA-harboring MET amplification and provides an alternative strategy for patients who are intolerant to chemotherapy.